PENGARUH KUALITAS PRODUK, HARGA DAN PACKAGING TERHADAP KEPUTUSAN PEMBELIAN BERAS RANTAU DI UD. PUTRA SULTAN - Verdiyanto, Verdiyanto; Fatimah, Feti; Hermawan, Haris (Growth, 2022)
The rapid development of today's business is increasingly dynamic, causing companies to be faced with conditions of intense competition, one of which is a company engaged in the sale of basic commodities, namely rice. The more businesses that have sprung up from time to time, the higher the number of similar businesses has been. This can tighten competition. So that at UD. Putra Sultan Besuki must create an attractive strategy for consumers. The purpose of this study was to test and analyze the effect of product quality, price and packaging on purchasing decisions at UD. Putra Sultan Besuki. This research uses a quantitative type with a descriptive approach. The population of this research is UD. Putra Sultan Besuki’s consumers who made purchases more than twice. 70 respondents were used as sample, and multiple linear regression analysis. The results show that product quality, price, and packaging have a positive and significant influence on purchasing decisions for Rantau Rice at UD. Putra Sultan Besuki.